KEDUDUKAN AKTA JUAL BELI SEBAGAI BUKTI KEPEMILIKAN HAK ATAS TANAH - Andri Pranata; Ade Indra Wardana (INTELIGENSIA MEDIA, 2023)
The Deed of Sale and Purchase is an authentic deed as the strongest evidence having an important role in every legal relationship in people's lives which can strictly determine rights and obligations so as to guarantee legal certainty and at the same time be able to avoid disputes. If there is a dispute over the authentic deed as evidence, it is the strongest evidence and has perfect evidentiary power in court. When an individual or group buys or sells land, they must enter into a sale and purchase contract or agreement. The contract must include information about the parties involved, the amount of money transferred, and a description of the land being sold. After that, the sale and purchase deed must be registered with the local land office to obtain a legal and official land certificate. It is this land certificate which then becomes proof of the legality and legitimacy of the ownership of the land, as well as providing legal certainty for the rights of ownership of the land. Therefore, it is very important for the land owner to register the deed of sale and purchase at the land office and obtain a valid and official land certificate. So the question is how strong is the Proof of the Deed of Sale and Purchase of Ownership of Land Rights and what are the reasons for an individual or group not registering land after carrying out a land sale and purchase transaction as evidenced by the Deed of Sale and Purchase. This research is normative legal research. Data collection techniques in this study are document studies and interviews, while the location of this research will be carried out in Samarinda City. The data that has been collected from library research and from field research is then analyzed qualitatively. The strength of proof of the deed of sale and purchase of land on the ownership of land rights has an important position in civil law. As an official document that transfers ownership of land rights from the seller to the buyer, the deed of sale and purchase of land has strong evidentiary power as legal proof of ownership of land rights. However, it is important to remember that the strength of the proof of the land sale and purchase deed also depends on several factors, such as the legality of the documents, land ownership status, payment and settlement of the selling price, and registration of the land sale and purchase deed with the BPN. Therefore, before buying land, it is important to ensure that the deed of sale and purchase of land is valid and meets the legal requirements in force in that country. There are several reasons why a person or group does not register land after carrying out a sale and purchase transaction as evidenced by a Sale and Purchase Deed, such as expensive registration fees, distrust of the government, and not knowing the procedure for land registration.